1998
DOI: 10.1093/oxfordjournals.pcp.a029295
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Cell Wall Involvement in Temporal Changes in Freezing Tolerance of Jerusalem Artichoke {Helianthus tuberosus L.) Tubers during Cold Acclimation

Abstract: We studied the mechanism of cold acclimation of Jerusalem artichoke (Helianthus tuberosus L.) tubers with special reference to the role of the cell wall. During the cold-acclimation process from September to January, the freezing tolerance of tubers increased from -2.8 degrees C to -8.4 degrees C (LT50). By contrast, the isolated protoplasts constitutively showed a consistent high level of freezing tolerance (LT50; below -25 degrees C) throughout the period. In tuber tissues, freezing injury was effectively pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
2
21
0
2
Order By: Relevance
“…Interestingly, the results shown in Figure 5 further revealed that the freezing tolerance of Arabidopsis leaf sections is considerably dependent on the osmolarity of the solution around leaf sections: in the presence of 1 mM calcium, survival of cells in leaf sections immersed in a solution without sorbitol was ;56% at -38C ( Figure 5A), but much greater (;70%) even at -128C when immersed in a solution containing 0.6 M sorbitol ( Figure 5B). This is consistent with the results of Murai and Yoshida (1998), who showed that the freezing tolerance of Jerusalem artichoke tuber tissues is remarkably lower in water than in an isotonic solution.…”
Section: Calcium-dependent Freezing Tolerance Of Leaf Sectionssupporting
confidence: 93%
“…Interestingly, the results shown in Figure 5 further revealed that the freezing tolerance of Arabidopsis leaf sections is considerably dependent on the osmolarity of the solution around leaf sections: in the presence of 1 mM calcium, survival of cells in leaf sections immersed in a solution without sorbitol was ;56% at -38C ( Figure 5A), but much greater (;70%) even at -128C when immersed in a solution containing 0.6 M sorbitol ( Figure 5B). This is consistent with the results of Murai and Yoshida (1998), who showed that the freezing tolerance of Jerusalem artichoke tuber tissues is remarkably lower in water than in an isotonic solution.…”
Section: Calcium-dependent Freezing Tolerance Of Leaf Sectionssupporting
confidence: 93%
“…However, this does not exclude the possibility of plasmolysis sensu stricto occurring in species where the rigidity of the cell wall does not allow folding in response to dehydration (Webb and Arnott 1982) or to extra-protoplasmic freezing (Murai and Yoshida 1998). Electron microscopy revealed that the plasmalemma maintains its trilaminar structure, continuity, and apposition against cell walls even at the very low water content of 0.08 g of water per g of dry mass.…”
Section: Discussionmentioning
confidence: 95%
“…Além do dano físico, podem ocorrer modificações na composição química da parede celular e na permeabilidade da membrana plasmática, que podem também influenciar na quantidade e qualidade do extrato final obtido (Palta et al, 1977;Olien & Smith, 1977;Chen & Gusta, 1978;Weiser et al, 1990;Murai & Yoshida, 1998).…”
Section: Armazenamento De Extratos E De Raízesunclassified
“…Em muitos estudos, a extração de sorgoleone tem sido feita a partir de raízes recém-coletadas, e o extrato é usualmente armazenado em baixas temperaturas antes da sua utilização em testes de atividade e do seu fracionamento (Einhelling & Souza, 1992;Rasmussen et al, 1992;Nimbal et al, 1996;Souza et al, 1999;Kagan et al, 2003;Czarnota et al, 2003b;Hejl & Koster, 2004). Alguns estudos mostram que o armazenamento de órgãos vegetais antes da extração pode acarretar alterações no extrato final obtido (Palta et al, 1977;Olien & Smith, 1977;Chen & Gusta, 1978;Weiser et al, 1990;Murai & Yoshida, 1998). Além disso, as condições de armazenamento de extratos vegetais podem influenciar na estabilidade e degradação dos compostos químicos presentes (Srivastava et al, 2007;Tabart et al, 2007).…”
Section: Introductionunclassified